Evaluation of the use of midazolam as a co‐induction agent with ketamine for anaesthesia in sedated ponies undergoing field castration. (29th September 2017) - Allison, A.; Robinson, R.; Jolliffe, C.; Taylor, P. M.
Summary: Background: There are limited investigations comparing ketamine to a ketamine‐midazolam co‐induction. Objectives: To compare quality and safety of general anaesthesia induced using ketamine alone with anaesthesia co‐induced using ketamine and midazolam. Study design: Randomised, double blinded, placebo controlled trial. Methods: After i.v. detomidine (20 μg/kg) thirty‐eight ponies undergoing field castration received either 0.06 mg/kg (0.6 mL/50 kg) midazolam (group M) or 0.6 mL/50 kg placebo (group P) with 2.2 mg/kg ketamine i.v. for anaesthetic induction. Quality of anaesthetic induction, endotracheal intubation, surgical relaxation and recovery were scored using combinations of simple descriptive and visual analogue scales. Time of sedation, induction, start of endotracheal intubation, first movement, sternal recumbency and standing were recorded, as were time, number and total quantity of additional i.v. detomidine and ketamine injections. Cardiorespiratory variables were assessed every 5 min. Adverse effects were documented. Data were tested for normality and analysed with a mixed model ANOVA, Fisher's exact test, unpaired Students' t test and Wilcoxon Rank‐sum as appropriate; P<0.05 was considered significant. Results: Group M had better scores for induction (P = 0.005), intubation (P<0.001) and surgical relaxation (P<0.001) and required fewer additional injections of detomidine and ketamine (P = 0.04). Time (minutes) from induction to first movement (P<0.001), sternal recumbency (P =< 0.001) and standing was longer (P = 0.05) in group M. Recoveries were uneventful with no difference in quality between groups (P = 0.78). Main limitations: Clinical study with noninvasive monitoring undertaken in field conditions. Conclusions: Ketamine‐midazolam co‐induction compared to ketamine alone improved quality of induction, ease of intubation and muscle relaxation without impacting recovery quality.